Universal Basic Income - Fajfar, Luka; Taškar Beloglavec, Sabina (Naše gospodarstvo/Our economy, 2014)
Universal basic income (UBI) is an alternative proposal to the current social system that provides unconditional basic income to every citizen in the amount of the mini- mum standard of living, regardless of social or employment status. UBI has become controversial due to the many years of discussion, during which two groups emer- ged with distinct perspectives of UBI: defenders and opponents. Critics have focu- sed mainly on its potential effects.